(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Fibromyalgia is a syndrome that manifests itself with the symptomatology of pain spread throughout the body (tender points), directly affecting the patient’s quality of life, as it compromises functionality, physical and psychological well-being. Aim: The aim of this study was to assess the quality of life, functional and physical capacity of patients with fibromyalgia. Methodology: This is a quantitative, exploratory and descriptive study, in which 12 patients were interviewed, 3 from the city of Nanuque/MG, 4 from the city of Ecoporanga/ ES, 3 from the city of Ponto Belo/ES and 2 through google forms, from May 18, 2023 to June 7, 2023. Results: When asked about the impact of fibromyalgia on their ability to perform everyday tasks, the following results were obtained in the never category: vacuuming the carpet (83%), walking several blocks (75%) and working outside (58%). The following symptoms were found: intense pain (83.33%), tiredness (83.33%), stiffness (50%), tension (66.67%) and depression (50%), as well as altered sleep quality (33.33% have moderate sleep and 66.67% have very poor sleep). Conclusion: It can be concluded that due to the intense pain caused by fibromyalgia, there are important limitations in patients’ lives, as it alters their functionality, interpersonal relationships and psychological state. However, physiotherapy plays a fundamental role, as it aims to treat symptoms such as pain, muscle shortening, muscle weakness, among others, thus promoting a better quality of life.